Analysis of Website Content Development Strategies to Increase Traffic for Riug Paragliding Bali - Farid Efendi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to explore the content strategies of the Riug Paragliding Bali website, specifically focusing on how these strategies influence purchasing decisions and their subsequent impact on sales improvement within the context of digital marketing. Given the competitive nature of the adventure tourism industry, understanding effective content strategies is crucial for attracting and retaining customers. The research method employed consists of in-depth interviews with four distinct groups of respondents: website visitors, customers who completed transactions, website developers, and the owners of Riug Paragliding. This diverse sample allows for a comprehensive analysis of different perspectives regarding the website's content effectiveness. The results of the study indicate that informative and engaging content plays a significant role in shaping consumers' purchasing decisions. Many respondents highlighted that detailed information regarding safety protocols, operational procedures, and customer testimonials enhances their trust in the services offered. This trust is vital in the adventure tourism sector, where safety concerns are paramount. Furthermore, both the owner and developers of the website recognized the importance of implementing appropriate content strategies to attract more visitors and improve sales conversion rates. These insights lead to recommendations for developing more effective content that aligns with digital marketing strategies, ultimately aiming to boost sales in the paragliding industry. By prioritizing quality content, Riug Paragliding can enhance its online presence and customer engagement, setting a benchmark for success in the competitive landscape of adventure tourism